Study of antenatal prevalence of HIV and its trend in a tertiary care hospital - Anand, Nikhil A.; Patel, Seema K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: HIV/AIDS has become a global problem since first detection in 1981.Women of childbearing age constitute nearly half of the 30 million adults currently living with HIV/AIDs worldwide. Pregnant women are considered as low risk for HIV so estimating prevalence in such low risk people provides us a good basis for long term strategy for implementation of HIV/AIDS control programme. The objective of this study was to study acceptance of antenatal HIV testing during routine ANC checkups using opt in strategy. To study prevalence of antenatal HIV and its trend. Methods: Observational and analytic study. Antenatal women coming for routine antenatal care in obstetric OPD were counseled and blood sample were taken according to guidelines for HIV testing from period 1/1/2014 to 31/12/2018. Results: Out of total 23907 women attending antenatal clinic 23841 accepted HIV testing, Out of these 72 were found positive, making HIV seroprevalence rate of 0.30. 42 spouses were also found positive. Conclusions: Though seroprevalence of HIV in antenatal women is low, slowly rising trend worths a caution for us.